The safety on a railway crossing by means of system of video analytics - Amochaeva, G.P.; Seisenbaeva, G.S.; Mussina, G.I. (Publishing House of the KarSU named after E.A. Buketov, 2018)
In this article we describe the development of technical requirements and software for video analytics used at railway crossings in order to determine the stopped vehicles. The work describes the scheme of the video analytics system, working observing zones, graphical illustrations of the video analytics system and its components. The program described in the work defines the stopped vehicles at the crossing and gives a signal to obstructing traffic lights to stop the locomotive. There are times when the program gives out the raw data. The program defines vehicles, but the fight against false positives implies the use of additional technical means.
Keywords: system of video analytics; railway crossing; working zone of the crossing; technological zone; zone of floor inventory